Potential Use of Cashew Apple (Anacardium occidentale L.) Powder as a Pharmaceutical Diluent in Simvastatin Tablets - Changsan, Narumon; Atipairin, Apichart; Muenraya, Poowadon; Srichana, Teerapol; Sritharadol, Rutthapol; Chanthorn, Wirot; Balekar, Neelam; Madting, Alawee; Sawatdee, Somchai (Science and Technology Indonesia, 2026)
This research aimed to create cashew apple powder (CAP) for use as a pharmaceutical diluent in tablet formulations and evaluate its suitability with simvastatin as a model drug. CAP was produced by grinding followed by milling for size reduction. CAP was incorporated as a diluent in simvastatin 20 mg tablets formulated using wet granulation and direct compression methods. CAP had light brown irregular particles. The median particle size (D50) was 282 ± 32 µm. True density was 1.408 g/cm3, bulk density was 0.405 g/cm3, and tapped density was 0.489 g/cm3. CAP had good flow properties and significantly better compaction properties than lactose monohydrate. There was no interaction between simvastatin and CAP based on FTIR and DSC analyses. Physical evaluation of the tablets prepared by the wet granulation method showed that hardness was 6.2 ± 0.6 kgf, disintegration time was 2.50 ± 0.75 minutes, % friability was 0.65% and assay simvastatin content was 101.22 ± 0.24 % LA. In the same manner, the tablets produced by direct compression had a hardness of 4.1 ± 0.2 kgf, disintegration time value of 0.83 ± 0.20 minutes, friability of 0.86%, and an assay simvastatin content of 102.65 ± 1.03% LA. Simvastatin tablets incorporating CAP showed complete drug release in 15 minutes. After 3 months of storage, no significant changes were recorded in the physicochemical properties, other than a slight increase in hardness for the wet granulation tablets. This study indicates that CAP can be considered a promising pharmaceutical excipient for immediate-release tablet formulations, compatible with both wet granulation and direct compression methods.